An experimental investigation on the anthelmintic efficacy of crude aqueous extracts of selected medicinal herbs against gastrointestinal helminths in native chickens - Tuyor, S.; Ramada, J. M. S. (Diponegoro University, 2025)
This study assessed the anthelmintic efficacy of selected crude aqueous herbal extracts against gastrointestinal helminths in native chickens raised under semi-scavenging conditions. Forty-five natu-rally infected birds were randomly allocated to five treatment groups: T1 (distilled water), T2 (commercial levamisole), T3 (Basella alba), T4 (Carica papaya), and T5 (Allium sativum). Treatments were administered orally at 3 mL/kg body weight, and fecal egg counts (EPG) were measured at base-line (day 0) and at days 10 and 14 post-treatment. Phytochemical analysis confirmed the presence of alkaloids, flavonoids, saponins, steroids, and tannins in all tested species. By Day 10, substantial reduc-tions in EPG occurred, with C. papaya (966.7 ± 76.4) and A. sativum (1100.0 ± 217.9) achieving sig-nificantly lower counts compared to distilled water (5283.3 ± 236.3) and the commercial anthelmintic levamisole (8650.0 ± 1468.3) (P < 0.05). B. alba exhibited intermediate efficacy (1233.3 ± 361.7), comparable statistically to the two most effective botanicals. However, EPG values rebounded signifi-cantly across all groups by day 14, though C. papaya (5166.7 ± 464.6), A. sativum (5266.7 ± 189.3), and B. alba (5250.0 ± 482.2) maintained significantly lower burdens compared to the control (10300.0 ± 3404.4) and levamisole (6716.7 ± 2878.5) groups (P < 0.05). These results show that botanical ex-tracts could be good short-term replacements for traditional anthelmintics. They also suggest that para-site control may require repeated or optimized dosing.